Simulation Model for Calculating the Route Time of a Vehicle. (2016) - Roib, Voichita Angela
Abstract: The paper presents a model created for the calculation of a vehicle route time between two chosen points: departure and arrival. The designed simulation model can be used for the calculation of route time, comparing route options and evaluating traffic management strategies. The goal is to provide the user with a representation of the network in real route time, starting from the data provided from the traffic data collection equipment.